Using language awareness techniques to improve the level of achievement in the english skills of the students taking a master's program in education in a private university - Lostaunau Gavidia, Jessie (2012)
The investigation has as its main objective to demonstrate if noticing or being aware of how the target language works can help students improve their learning language skills. It pretends to find the best tools to help adult students to learn another language. Likewise, it intends to contribute with ideas to help teachers who may find themselves in the same situation as the one presented in this investigation.